Company Value through Financial Performance as Intervening Variables: Capital Structure and Proportion of The Board of Commissioners - Mella Putri Dwiba (Journal of Business and Economics (JBE) UPI YPTK, 2021)
firm value with financial performance as an intervening variable. The object of research is various industrial companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The type of data used in this study is quantitative data using the purporsive sampling method. The sample in this study were various industrial companies listed on the Indonesia Stock Exchange as many as 25 companies. The analytical method of this research is to use multiple regression analysis techniques and path analysis with the SPSS version 25.0 application. The results of this study indicate that the partial test with Intervening (1) Capital Structure has a positive and significant effect on the financial performance variable in the company (2) the proportion of the board of commissioners has no and significant effect on the financial performance variable in the company. And by partial test before Intervening (3) Capital Structure has a significant and significant effect on the Firm Value variable (4) The proportion of the board of commissioners has no effect on the Firm Value variable (5) Financial performance has a significant and significant effect on the Firm Value variable. And the results of the research based on the path test (6) Capital structure which is intervened by the financial performance variable has an effect and is significant on the Firm Value variable (7) The board of commissioners intervened by the financial performance has an effect and is significant on the Firm Value variable.